Germline excision of the transposable element Tc1 in C. elegans. - Moerman, D G (1991)
We have examined eight germline revertants generated by the excision of Tc1 from a site within the unc-22 gene of Caenorhabditis elegans. A rich variety of rearrangements accompanied Tc1 excision at this site, including transposon 'footprints', deletions of sequences flanking the insertion site and direct nontandem duplications of flanking DNA. With only modest modification the double-strand gap repair model for transposition, recently proposed by Engles and coworkers (Cell 62: 515-525 1990), can explain even the most complex of these rearrangements. In light of this model rearrangements of the target site accompanying transposition/excision may not be the end result of imprecise excision of the element. Instead, these rearrangements may be the result of imprecise repair of the double-strand gap by the host replication and repair machinery. Sequences surrounding an insertion site influence the fidelity of gap repair by this machinery. This may lead to a number of possible resolutions of a double-strand gap as documented here for a Tc1 site in unc-22.